(untitled) (Sustainability in Debate, 2013)
The world population is expected to reach 9 billion by 2050, which will put greater pressure on natural resources to ensure the nutritional requirements and well-being for such a large population. Enormous investments in agricultural research, health, energy sources, material technologies, policies for poverty reduction and strategies for sustainable development must be made to meet this scenario. Actions to conserve natural resources and ecosystem services are implicit in sustainable development strategies. An increase in the number of public policies being implemented, their results, ongoing projects and research related to environmental conservation are being observed and attest to their current and future relevance.